2013
DOI: 10.1097/brs.0000000000000019
|View full text |Cite
|
Sign up to set email alerts
|

Extremely Wide and Asymmetric Anterior Decompression Causes Postoperative C5 Palsy

Abstract: Extremely wide and asymmetric decompression concomitant with pre-existing C4-C5 foraminal stenosis may cause postoperative C5 palsy. Our findings should be valuable for surgeons considering anterior cervical decompression and fusion that includes the C4-C5 level. Surgeons should consider restriction of the decompression width to less than 15 mm and avoiding asymmetric decompression to reduce the incidence of C5 palsy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 16 publications
(1 reference statement)
1
37
0
Order By: Relevance
“…found that 32 (7%) experienced postoperative C5 palsies [Tables 1 and 2 ]. [ 18 ] They were divided into two groups (palsy side [ n = 35] and nonpalsy side [ n = 29]), and their clinical/radiographic studies were compared with 66 consecutive other patients who had the same procedures without C5 root deficits. They found that those with C5 palsies had smaller preoperative C4-C5 foramina, underwent more extensive/wider/asymmetric unilateral decompressions, and exhibited less anterior spinal cord shift.…”
Section: Risk Of C5 Palsy With Anterior Cervical Decompressionmentioning
confidence: 99%
“…found that 32 (7%) experienced postoperative C5 palsies [Tables 1 and 2 ]. [ 18 ] They were divided into two groups (palsy side [ n = 35] and nonpalsy side [ n = 29]), and their clinical/radiographic studies were compared with 66 consecutive other patients who had the same procedures without C5 root deficits. They found that those with C5 palsies had smaller preoperative C4-C5 foramina, underwent more extensive/wider/asymmetric unilateral decompressions, and exhibited less anterior spinal cord shift.…”
Section: Risk Of C5 Palsy With Anterior Cervical Decompressionmentioning
confidence: 99%
“…The incidence of this complication has been reported to be between 0% and 30% depending on procedure type and approach. 1-36 Patients commonly present with new weakness in the deltoid and/or biceps brachii, sensory deficits, and/or pain in the shoulders, and dissatisfaction with surgery *. C5 palsy may present immediately after surgery or up to 2 months postoperatively † and can negatively affect postoperative quality of life in the short term.…”
Section: Introductionmentioning
confidence: 99%
“…In regard to the C4/5 foraminal stenosis, the mean diameters of C4/5 foramen with C5 palsy were reported below 2.7 mm [24]; however, that of this patient was 3.5 mm. No left C4/5 foraminal stenosis in the intraoperative findings also supports the spinal cord lesion responsible for C5 palsy.…”
Section: Discussionmentioning
confidence: 86%
“…Although the nerve root tethering produced by spinal cord shifting after spinal cord decompressive surgery is now becoming a leading hypothesis [24], the cause of C5 palsy is still controversial and the spinal cord lesion is also hypothesized as the probable mechanism [5, 6]. …”
Section: Introductionmentioning
confidence: 99%